Answer :

Let I =

⇒

⇒

⇒

⇒

⇒

⇒

Let sinx + cosx = t

⇒ (cosx-sinx)dx = dt

Therefore, I =

⇒

⇒

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

RELATED QUESTIONS :

Write a value of

RD Sharma - Volume 1Mark (√) against the correct answer in each of the following:

RS Aggarwal - Mathematics

Evaluate the following integrals:

Mark (√) against the correct answer in each of the following:

RS Aggarwal - Mathematics

Write a value of

RD Sharma - Volume 1Evaluate the following integrals

RS Aggarwal - Mathematics

Evaluate the following integrals:

RD Sharma - Volume 1

Evaluate the following integrals:

RD Sharma - Volume 1

Evaluate the following integrals –

RD Sharma - Volume 1

Mark (√) against the correct answer in each of the following:

RS Aggarwal - Mathematics